The Relationship Between the Level of Knowledge of the Elderly About Risk Factors of Low Back Pain and the Incidence of Low Back Pain at Pusat Pelayanan Sosial Lanjut Usia Mandalika, Nusa Tenggara Barat, in 2025 - Lioni, Ni Kadek; Wedayani, Anak Agung Ayu Niti; Purnaning, Dyah; Adni, Azizatul (Jurnal Biologi Tropis, 2026)
Low Back Pain (LBP) is a musculoskeletal problem that is often experienced by the elderly and can reduce the quality of life. Knowledge of LBP risk factors plays an important role in efforts to prevent and treat it. This study aims to determine the relationship between the level of elderly knowledge about LBP risk factors and the incidence of LBP at the Mandalika Elderly Social Service Center, West Nusa Tenggara in 2025. This quantitative study used a cross-sectional design on 41 elderly people selected through total sampling. Data was collected using a questionnaire that had been tested for validity and reliability, then analyzed univariately and bivariously with Chi-square test. The results showed that most of the respondents had sufficient knowledge (46.3%), followed by low (34.1%) and good (19.5%) knowledge. The incidence of LBP was found in 26 respondents (63.4%), while 15 respondents (36.6%) did not experience LBP. The Chi-square test showed a significant relationship between the level of knowledge of the elderly and the incidence of LBP (p-value = 0.002). It was concluded that low knowledge was related to the high incidence of LBP. Continuous health education is needed to increase the understanding of the elderly in preventing LBP.